2016
DOI: 10.1097/jcp.0000000000000495
|View full text |Cite|
|
Sign up to set email alerts
|

Relation of the Allelic Variants of Multidrug Resistance Gene to Agranulocytosis Associated With Clozapine

Abstract: Clozapine use is associated with leukopenia and more rarely agranulocytosis, which may be lethal. The drug and its metabolites are proposed to interact with the multidrug resistance transporter (ABCB1/MDR1) gene product, P-glycoprotein (P-gp). Among various P-glycoprotein genetic polymorphisms, nucleotide changes in exons 26 (C3435T), 21 (G2677T), and 12 (C1236T) have been implicated for changes in pharmacokinetics and pharmacodynamics of many substrate drugs. In this study, we aimed to investigate the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…There has been a recent interest in a pharmacokinetic mechanism via polymorphisms within ABCB1 , the P-glycoprotein transporter gene responsible for the excretion of major clozapine metabolites, as there is evidence they effect clozapine plasma levels [67,68]. However, there is very limited evidence to date to suggest they cause CIN or CIA [48,69].…”
Section: Risk Variants For Clozapine-associated Neutropeniamentioning
confidence: 99%
“…There has been a recent interest in a pharmacokinetic mechanism via polymorphisms within ABCB1 , the P-glycoprotein transporter gene responsible for the excretion of major clozapine metabolites, as there is evidence they effect clozapine plasma levels [67,68]. However, there is very limited evidence to date to suggest they cause CIN or CIA [48,69].…”
Section: Risk Variants For Clozapine-associated Neutropeniamentioning
confidence: 99%
“…10 In our clinic, a possible role of MDR1 genotypes on clozapine-induced agranulocytosis was previously suggested. 11 Direct toxicity of clozapine is suggested to be another possible mechanism. 12 It may affect common apoptotic pathways, also activated by chemotherapy, but overlapping of these effects is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The ABCB1 variant rs1045642 AA genotype (3435G>A) is associated with increased plasma clozapine [36]. The same genotype of ABCB1 rs1045642 was also associated with agranulocytosis and neutropenia [81] but another study found that this genotype, when part of a haplotype of ABCB1, might be protective against agranulocytosis [82]. In general clozapine induced agranulocytosis is not thought to be dose dependent but increased drug concentrations specifically in leukocytes could be a factor and may be influenced by genetic variants.…”
Section: Pharmacogenomicsmentioning
confidence: 99%